"OPTIMIZING FRONTEND APPLICATION PERFORMANCE: BEST PRACTICES AND MODERN TOOLS" (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The efficiency of frontend applications is a pivotal element in contemporary web development, directly shaping user interaction and the overall success of digital products. This paper delves into crucial optimal strategies and current tools designed to enhance frontend application performance, with a specific focus on metrics such as Largest Contentful Paint (LCP) and First Input Delay (FID). It examines the role of instruments like Lighthouse and Vite, alongside modern frameworks including React and Svelte, in achieving performance improvements. Through the analysis of practical examples and technical evaluations, this paper outlines actionable methods for constructing user interfaces that are fast, responsive, and resource-efficient.